PENGARUH CITRA MEREK, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE - Mohamad Ravi Aditama, (2022)
This study aims to determine the influence of brand image varaibel, product quality and price on the purchasing decision of iphone smarthphones (Case study of iphone smartphone consumers within the Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta). In the study conducted using quantitative research, the sample number of samples in this study was as high as 100 people. The sampling technique that will be used in this study is non probability sampling with purposive sampling method by distributing questionnaires. The data analysis techniques used are descriptive analysis and inferential analysis assisted by Partial Least Square (PLS) analysis tools in the form of SmartPLS 3.0 and by using hypothesis tests, namely determination efficiency tests and static tests using a signification rate of 5%(0.05). The results of the test were obtained (1) there is a positive and significant influence of brand image on purchasing decisions (2) there is a positive and significant influence on product quality on purchasing decisions (3) there is a positive and significant influence between price on purchasing decisions